A multiple-control system for nonlinear discrete object under uncertainty. (4th May 2019) - Kolesnikova, S. I.
ABSTRACT: The algorithm for the analytical synthesis of a control system for a nonlinear object with random uncertainty in a description is proposed. The idea of the algorithm goes back to the method of analytical design of aggregated regulators, developed only for deterministic objects. It is shown that both algorithms can demonstrate different quality of control in different areas of the phase space. Therefore, the algorithm is proposed for constructing a multiple control system for a nonlinear object without preliminary linearization. The algorithm is based on an algebraic approach to the synthesis of correct algorithms by a set of basic algorithms. In this case, aposteriori information on the quality of control in the state space of an object is used.